Modelling framework for flight dynamics of flexible aircraft - Portapas, Vilius; Cooke, Alastair K.; Lone, Mudassir M. (Vilnius Gediminas Technical University Press, 2016)
The flight dynamics and handling qualities of any flexible aircraft can be analysed within the Cranfield Aircraft Accelerated Loads Model (CA2LM) framework. The modelling techniques and methods used to develop the framework are presented. The aerodynamic surfaces were modelled using the Modified Strip Theory (MST) and a state-space representation to model unsteady aerodynamics. With a modal approach, the structural flexibility and each mode’s influence on the structure deflections are analysed. To supplement the general overview of the framework equations of motion, models of atmosphere, gravity, fuselage and engines are introduced. The AX-1 general transport aircraft model is analysed as an example of the CA2LM framework capabilities. The results showed that, according to the Gibson Dropback criterion, the aircraft with no control system lacks the stability and its longitudinal handling qualities are unsatisfactory. Finally, the steps for future developments of the CA2LM framework are listed within conclusions.
Keywords: aeroelasticity; flexible aircraft; flight dynamics; handling qualities